Pulse width compression technology of high-energy laser for Thomson scattering diagnostics - Jian Zhou; Shumei Xiao; Qing Zang; Wen Chu (AIP Advances, 2025)
The laser beam with a narrow pulse width enhances the signal-to-noise ratio of the Thomson scattering system. A laser system’s chopping module has been designed to compress the pulse width to improve the peak power. The chopping module is positioned between the oscillator and the first amplification stage and comprises Pockels cells, a high-voltage module, and polarizers. Precise control of pulse width is achieved through synchronization with the laser’s Q-switch system. A narrow pulse width laser has been assembled and put into operation. Measurements indicate that the pulse width of the laser has been reduced from 24.608 to 3.408 ns, with an average output energy of ∼1.028 J. This technology is expected to greatly improve the measurement accuracy of the system.